Realia To Improve Students' Writing On Descriptive Paragraph; An Experimental Design - Maria Astuti BidaTolok (Language-Edu, 2020)
The study was aimed to measure the effectiveness of realia in teaching writing descriptive paragraph at junior high school students. The design employed was pre- experimental. The subject was one of the class of eight grade at SMPN 2 Malang. The samples were 32 students of this study. The data was collected from pretest and posttest score. During six meetings for treatments and two meetings for pretest and posttest. The students were given writing test using writing test. The data was investigated using t-test of IBM SPSS 20. The data were analyzed by comparing the mean of students’ scores of pretest and posttest. Based on the statistical analysis, it could be comprehended from the result of mean score of posttest of students is 75.31 and the mean score of pretest 49.06. Then, the t-test (20.35) was higher than t critical value (2.04) at a level of significance 0.05. Thus, it can be established that who were taught by using realia had a enhanced performance in learning writing especially on descriptive paragraph.Keywords: effectiveness of realia, writing descriptive paragraph